Uruguay : 2019 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Uruguay. (IMF Staff Country Reports; Country Report ;, 2020)
This 2019 Article IV Consultation with Uruguay highlights that the country enjoys political stability, strong governance and institutions, and a high degree of social cohesion. Following a decade and a half of robust growth, the country boasts high per capita income, low levels of poverty and inequality, and a resilient financial sector. More recently, in a context of a volatile region and global uncertainties, challenges have emerged. The political and economic landscapes-with the post-election mandate and a growth boost due to large private and infrastructure investments-present an opportunity to address these challenges and preserve the social compact for future generations. The authorities are expected to use the opportunity to reduce debt and bring inflation toward the mid-point of the target range, to rebuild buffers and manage sizable risks. In addition, the authorities should leverage Uruguay's institutional advantages to further improve the fiscal and inflation targeting frameworks and implement structural reforms, in order to raise potential growth and safeguard the achievements of the past decade.